التنافس الأمريكي الروسي في منطقة الساحل الأفريقي وتداعياته الجيوسياسية (Journal of Academic Research, 2025)
AbstractThe Sahel is a region of growing geopolitical importance, currently witnessing intense competition between major powers, particularly the United States and Russia. This research aims to analyze the nature of this competition, its motivations, tactics, and implications for the countries of the region and broader international relations. It also examines the strategic motivations of both the United States and Russia, their distinct tools of engagement (including military proxies, media, security assistance, and diplomatic efforts), the impact of regional political dynamics such as military coups on this competition, and the broader implications for the Sahel countries and international relations.